Assessment of poliovirus antibody seroprevalence in high risk areas for vaccine derived poliovirus transmission in Madagascar. Issue 3 (March 2018) - Razafindratsimandresy, Richter; Mach, Ondrej; Heraud, Jean-Michel; Bernardson, Barivola; Weldon, William C.; Oberste, M. Steven; Sutter, Roland W.
Abstract: Background: Vaccine-derived polioviruses (VDPV) outbreaks typically occur in areas of low poliovirus immunity. Madagascar successfully eradicated wild poliovirus in 1997; however, multiple VDPV outbreaks have occurred since then, and numerous vaccination campaigns have been carried out to control the VDPV outbreaks. We conducted a survey of poliovirus neutralizing antibodies among Malagasy children to assess performance of vaccination campaigns and estimate the risk of future VDPV outbreaks. Methods: This was a random community survey in children aged 6–11 months, 36–59 months and 5–14 years of age in high risk areas of Madagascar (Mahajanga, Toliara, Antsalova, and Midongy-atsimo); and in a reference area (Antananarivo). After obtaining informed consent, basic demographic and vaccination history, 2 mL of peripheral blood were collected. Neutralizing antibodies against all three poliovirus serotypes were detected by using a standard microneutralization assay. Results: There were 1500 children enrolled and 1496 (>99%) provided sufficient quantity of blood for analysis. Seroprevalence for poliovirus type 1 (PV1) was >90% in all age groups and study areas. PV2 seroprevalence ranged between 75–100%; it was lowest in the youngest age group in Midongy and Toliara. PV3 seroprevalence ranged between 79–100%. Seroprevalence in the reference area was not significantly different from polio high risk sites. Discussion: Madagascar achieved high population immunity. In order to preserve these gains, routine immunization needs to be strengthened. Currently, the risk of new VDPV emergences in Madagascar appears low.